Hepatic lead and copper concentrations in dogs with chronic hepatitis and their relationship with hematology, serum biochemistry, and histopathology. (22nd May 2021) - Gori, Eleonora; Pierini, Alessio; Meucci, Valentina; Abramo, Francesca; Muscatello, Luisa V.; Marchetti, Veronica
Abstract: Background: Although the influence of copper ([Cu]) on chronic hepatitis (CH) has been widely studied in dogs, little information is available about the accumulation of other metals. Hypothesis/Objectives: We assessed the concentration of lead ([Pb]) in the livers of dogs with CH with or without abnormal hepatic [Cu] to establish if any association existed between [Pb] and either hematologic or biochemical variables, fibrosis, necrosis and inflammation of the liver on histology. Animals: Thirty‐four dogs with CH that had hepatic [Cu] and [Pb] determined. Methods: Retrospective review of medical records of dogs with CH and hepatic [Cu] and [Pb]. Chronic hepatitis was defined using current American College of Veterinary Internal Medicine consensus statement guidelines. Hepatic [Cu] and [Pb] were determined using square wave anodic stripping voltammetry. Dogs were divided into 2 groups based on [Cu]: <400 ppm (LoCu) and ≥400 ppm (HiCu). Results: The median [Cu] and [Pb] were 357 ppm (range, 100‐7743 ppm) and 58.7 (range, 6.89‐224.4 ppm), respectively. Nineteen dogs had LoCu and 15 dogs had HiCu. Median [Pb] was significantly higher in HiCu compared to LoCu dogs ( P  < .001). Hepatic [Pb] and [Cu] were significantly correlated (rho = 0.7; P  < .001). Dogs with microcytosis had higher [Pb] than did dogs with normal red cell volume ( P  = .02). Hepatic [Pb] was not correlated with either necroinflammatory or fibrosis scores. Conclusions and Clinical Importance: Although additional studies are needed to better understand the clinical role of hepatic [Pb], dogs with abnormal hepatic [Cu] may also have higher hepatic [Pb]. In addition, in dogs with high hepatic [Pb], microcytosis may be present.